Characteristics of microstructural phenomena occurring on the surface of protective gloves by the action of mechanical and chemical factors - Irzmańska, E.; Dyńska-Kukulska, K.; Jurczyk-Kowalska, M. (Polimery, 2014)
The aim of this study was to evaluate the microstructural changes on the surface of glove materials used in the workplace — new and subject to mechanical and chemical interactions in both simulated conditions in a laboratory and on actual jobs. The introductory part presents a brief review concerning application of the scanning electron microscope technique to characterize the microstructural phenomena occurring on the surface of textiles used to construct protective gloves. Research has indicated that ascanning electron microscope can be used to characterize the microstructural phenomena occurring on the surface of the materials exposed to mechanical and chemical harmful factors. Based on the results, it was found that the impact of the proposed conditions has a different influence on the morphology of the rubber surface: acrylonitrile-butadiene and chloroprene. In both cases there are different morphological features characterizing particular types of changes observed on the surface.